Law Enforcement in Criminal Acts of Narcotics Smuggling in Maritime Areas - Wattimena, Ricky Marthen (IHSA Institute, 2025)
Combating narcotics smuggling via maritime routes poses a considerable challenge for Indonesia due to its expansive territorial waters and the prevalence of small, unregulated ports that are often exploited by transnational criminal organizations. This research aims to evaluate the effectiveness of law enforcement in addressing maritime drug trafficking and to examine the roles of major enforcement bodies, including the Indonesian National Police, the Directorate General of Customs and Excise, and the National Narcotics Agency. Utilizing a normative juridical research approach, the study is grounded in legal theory and statutory analysis. The findings reveal that the majority of narcotics enter Indonesia through sea routes using increasingly advanced smuggling techniques. However, enforcement efforts are hampered by limitations in human resources, surveillance infrastructure, and inter-agency coordination. Existing legal and operational measures have proven inadequate in deterring or prosecuting maritime drug crimes. The study concludes that strengthening maritime surveillance systems, enhancing institutional cooperation, and fostering community involvement are essential to effectively combat narcotics trafficking in Indonesian waters. Furthermore, legal reforms are necessary to adapt law enforcement strategies to the complex and transnational dynamics of organized drug crime